Implementation of a rapid assay of ADAMTS13 activity was associated with improved 30‐day survival rate in patients with acquired primary thrombotic thrombocytopenic purpura who received platelet transfusions. Issue 8 (12th May 2017) - Yoshii, Yumi; Fujimura, Yoshihiro; Bennett, Charles L.; Isonishi, Ayami; Kurumatani, Norio; Matsumoto, Masanori
Abstract : BACKGROUND: Platelet (PLT) transfusions are probably harmful in patients with acquired idiopathic thrombotic thrombocytopenic purpura (aTTP). Introduction of a rapid assay for ADAMTS13 activity should reduce the time to definite diagnosis of aTTP, reduce the amount of inappropriately transfused PLT concentrates, and improve mortality and morbidity. STUDY DESIGN AND METHODS: We selected 265 aTTP patients with severe ADAMTS13 deficiency. Of these, 91 patients were diagnosed by March 2005 (Period 1), when ADAMTS13 activity was measured by von Willebrand factor multimer assay, which took 4 to 7 days until the result was reported. An additional 174 patients were diagnosed after April 2005 (Period 2), when the activity was measured by a chromogenic enzyme‐linked immunosorbent assay, which took 1 to 2 days. RESULTS: We found no significant differences in 30‐day survival rate between the two periods. Overall, 48 patients received PLT transfusions. Mortality was slightly greater between patients with (22.9%) versus without PLT transfusion (17.7%), but not significant. In Period 1, Cox proportional hazards regression analysis showed that older age (≥60 years) and PLT transfusion administration were independent factors associated with higher risks of 30‐day mortality. In contrast, in Period 2, lower Rose‐Eldor TTP severity score and use of plasma exchange and corticosteroid therapy were independent factors associated with higher survival rates while nonadministration of PLT transfusions was not. CONCLUSION: Our results indicate that PLT transfusions are harmful for aTTP patients when the definite diagnosis of severe ADAMTS13 deficiency is delayed. If it can be done as soon as possible, PLT transfusions for severe bleeding or surgical interventions might be allowed with subsequent plasmapheresis.